The p-adic potts model on the cayley tree of order three - Mukhamedov, Farrukh; Akin, Hasan (Springer Link, 2013)
We study a phase transition problem for the q-state p-adic Potts model on the Cayley tree of order three. We find certain conditions for the existence of p-adic Gibbs measures and then establish the existence of a phase transition.